2011
DOI: 10.1152/ajplung.00069.2011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of postnatal growth trends in proximal pulmonary arteries in rats by phase-contrast magnetic resonance imaging

Abstract: Malformations of the pulmonary arteries can increase right heart workload and result in morbidity, heart failure, and death. With the increased use of murine models to study these malformations, there is a pressing need for an accurate and noninvasive experimental technique that is capable of characterizing pulmonary arterial hemodynamics in these animals. We describe the growth trends of pulmonary arteries in 13 male Sprague-Dawley rats at 20, 36, 52, 100, and 160 days of age with the introduction of phase-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our PCMRI techniques (29) have enabled in vivo measurements of vessel size and pulmonary flow that indicate that pulmonary arterial banding results in lowered flow and smaller lumen sizes throughout development. We show, for the first time, that the wall shear autoregulatory phenomenon (18,32,43) that has been proposed as the biomechanical factor dictating vessel caliber in systemic arteries also holds in the case of the pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our PCMRI techniques (29) have enabled in vivo measurements of vessel size and pulmonary flow that indicate that pulmonary arterial banding results in lowered flow and smaller lumen sizes throughout development. We show, for the first time, that the wall shear autoregulatory phenomenon (18,32,43) that has been proposed as the biomechanical factor dictating vessel caliber in systemic arteries also holds in the case of the pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of pulmonary arterial blood flow in vivo were conducted according to techniques described previously in detail (29).…”
Section: Pcmri Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transthoracic two-dimensional and pulsed-wave Doppler modes were used to obtain the triplet of main pulmonary artery (PA) diameter measurements and the five velocity-time integral measurements close to the center of the vessel. Echocardiographically derived cardiac output was calculated with the formula [(main PA area) ϫ (main PA velocity-time integral) ϫ heart rate] as published previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…The number of repeat measurements is limited only by exposure to radiation, which applies largely to CAT studies. Indeed, studies have reported the monitoring of postnatal pulmonary artery growth at regular intervals for up to 160 days by phase-contrast MRI (22), highlighting the usefulness of noninvasive, nonterminal radiological approaches to study lung structure and function. In terms of airway function, synchrotron radiation computed tomography (CT) imaging has recently been very elegantly used to differentiate central vs. peripheral airway and lung parenchymal components of the response to airway provocation by cigarette smoke (19), and single proton emission computed tomography (SPECT) to quantify clearance of intratracheally delivered 99m Tc-diethylene triamine pentaacetic acid has been used to assess airway barrier function (26).…”
mentioning
confidence: 99%